Papel estratégico do agente de crédito para a sustentabilidade do microcrédito produtivo orientado: o caso do Crediamigo (BNB) - Souza, Natália de Olivindo (2018)
Oriented Productive Microcredit (OPM) can be understood as a productive financial insertion policy aimed at micro entrepreneurs excluded by the conventional financial system. One of its main innovations is the credit agent who acts in direct contact with them. Such methodology is used in the Crediamigo program, a major feature in the national micro financial section. In this way, this thesis’ main objective is to analyze the strategic role of the credit agent in OPM’s sustainability, by studying the case on BNB’s Crediamigo program. More specifically, the objectives are i) to present an overview on Crediamigo; ii) to assess the profile of the program’s credit agent; iii) to identify the common/specific aspects related to the acting of said credit agent and iv) to analyze the group of routine actions by the credit agent, grouping them to the observations in the Main-Agent models in the OPM context. The databases used are primary-based types extracted from question forms sent to a select group of Crediamigo’s credit agents, field work and interviews as well as secondary-based types when the secondary data in the BNB-INEC system were used. The methodology comprises the exploratory analysis of data by the descriptive method and multivariate analyzes such as factorial analysis and multidimensional scaling. Among the results, we highlight the ones from the research on the two main-agent relations found in the context of OPM. The influence of the institutional-organizational basis of the program on the profile of this professional is highlighted, which is effectively assigned to a strategic role. The profile of the credit agent population also revealed that this is a young population, which has had other professional experiences, has an average of three years in the program, has educational levels consistent with the application of the technical functions intended. They are also responsible for pocket books which can be considered productive and which allow the use of supportive pledge. By the factorial analysis, the results showed that 24 representative variables were compacted in 4 factors: Transmission and efficiency of incentives (F1); Financial, social and sustainability mission (F2); Objectives’ efficiency (F3) and Objective’s divergence (F4). By the traced profile of what the key dimensions of the EMD found by the sample data would be, these were named Incentives and Mission. The interaction of the results showed that it is indeed crucial to deal with the credit agent's strategic role in OPM's sustainability, the recognition of its potentialities by the microfinance institution and that it enables the minimization of information asymmetry in the creditor-borrower relationship, the latter which can be treated as a second-best solution.